Evaluation of clinical findings and treatment options of Sydenham chorea patients - Yimenicioğlu, Sevgi; Kosger, Pelin (Journal of Surgery and Medicine, 2021)
Background/Aim: Sydenham chorea is an autoimmune neurological disorder of the childhood which occurs due to cross-reaction of antibodies against group A beta-hemolytic streptococci in the basal ganglia. We evaluated patients with Sydenham’s chorea, treatment options, recovery duration, and relapses to determine whether there is any relationship between biochemical parameters such as erythrocyte sedimentation rate (ESR), serum Anti Streptolysin Antibody (ASA), and patients’ clinical course. Methods: This case series includes patients with Sydenham chorea who visited the pediatric neurology outpatient clinics between May 2013 and September 2018. Neurologic examination was performed by a pediatric neurologist, and electrocardiography and echocardiography were performed by a pediatric cardiologist. ESR and ASA levels, treatment options, and clinical course of the disease were evaluated. Results: Sixteen patients, with nine females (56.3%) and seven males (43.7%) were included in this study. The most seen chorea type was hemichorea. The median ASA and ESR values of the patients were 619 IU/ml (278.25-794.75) and 17.5 mm/h (7.25-27), respectively. Their median age and time until recurrence were 12 (9-14.25) years and 16 months (9-18), respectively. The median recovery period was 5.5 months (3-6). Diazepam and haloperidol were the most used secondary treatment options. Mitral insufficiency (MI) was the most frequent finding (56.3%). Benzathine penicillin and secondary prophylaxis, e.g., haloperidol, diazepam were our treatment agents of choice. ASA levels were lower among patients treated with steroids (U=9, z=-2.38, P=0.017). Age was moderately positively correlated with recovery period (age r (14) = 0.738, P=0.001)), while no correlation was found between age and ESR, or recurrence period (P=0.98, P=0.33, respectively). The recovery period of generalized chorea was longer than that of hemichorea (U=10.5, z=-1.96, P=0.05). Recurrence was not related to ASA levels, ESR levels, age, or recovery period (P=0.73, P=0.89, P=0.78, P=0.83 respectively). Conclusion: High ASA levels may not indicate steroid need, and the recovery period increases with age and in cases of generalized chorea. Instead of benzathine penicillin or other known secondary prophylactic agents, azithromycin and levetiracetam can be used in hypersensitive patients.